Answer:
f(9) = f(8)·(-3)
Step-by-step explanation:
A recursive function is one where each successive term is calculated using the previous term;
The clear pattern demonstrated in the sequence of terms shown is that each term is multiplied by -3 to give the next one;
Hence, the correct option is the first.
Answer:
0.3333333333333...........
3
is the simplify expression
Step-by-step explanation:
Answer:
The sum of the given series is 1023
Step-by-step explanation:
Geometric series states that a series in which a constant ratio is obtained by multiplying the previous term.
Sum of the geometric series is given by:
where a is the first term and n is the number of term.
Given the series: ![1+2+4+8+.................+a_{10}](https://tex.z-dn.net/?f=1%2B2%2B4%2B8%2B.................%2Ba_%7B10%7D)
This is a geometric series with common ratio(r) = 2
We have to find the sum of the series for 10th term.
⇒ n = 10 and a = 1
then;
![S_n = \frac{1(1-2^{10})}{1-2} =\frac{1-1024}{-1} =\frac{-1023}{-1}=1023](https://tex.z-dn.net/?f=S_n%20%3D%20%5Cfrac%7B1%281-2%5E%7B10%7D%29%7D%7B1-2%7D%20%3D%5Cfrac%7B1-1024%7D%7B-1%7D%20%3D%5Cfrac%7B-1023%7D%7B-1%7D%3D1023)
Therefore, the sum of the given series is 1023
Answer
: 4.5
Step-by-step explanation:
a^2+b^2=c^2
4^2+2^2=20
Square root of 20 = 4.5